Negosiasi Gender dan Politik Identitas dalam Praktik Pencatatan Pernikahan: Kajian Komunikasi Politik Islam di Deli Serdang - Ferry, Muhammad; Azhar, Anang Anas; Nasution, Hasyimsyah (Medan Resource Center, 2025)
This study investigates the dynamics of gender negotiation and identity politics in shaping marriage registration practices in Deli Serdang, Indonesia. Employing a qualitative case study approach, it focuses on the interaction among religious authority, ethnic traditions—particularly within Malay and Batak communities—and state legal frameworks. The research finds that many unregistered marriages gain legitimacy through discourses of Islamic identity and customary norms, where women’s agency is often curtailed by structural factors such as economic dependence and entrenched patriarchal values. Religious leaders frequently prioritize syar’i legitimacy over civil legal recognition, influencing community perceptions and practices. Furthermore, state efforts to promote marriage registration—typically via religious sermons and administrative outreach—are largely top-down, failing to engage deeply with local sociocultural realities. In contrast, civil society actors such as the Congress of Indonesian Women Ulama (KUPI) adopt more inclusive and participatory communication models. KUPI’s approach integrates the ethical aims of Shariah (maq??id al-shar?‘ah) with constitutional legality, while simultaneously enhancing women’s roles in decision-making processes. This study emphasizes the need for dialogic, community-based communication strategies that align legal reforms with lived religious and cultural experiences, ultimately advocating for justice-oriented and gender-responsive marriage registration policies.